Psychophysiological effects of slow‐paced breathing at six cycles per minute with or without heart rate variability biofeedback. (11th October 2021) - Laborde, Sylvain; Allen, Mark S.; Borges, Uirassu; Iskra, Maša; Zammit, Nina; You, Min; Hosang, Thomas; Mosley, Emma; Dosseville, Fabrice
Abstract: Heart rate variability (HRV) biofeedback, referring to slow‐paced breathing (SPB) realized while visualizing a heart rate, HRV, and/or respiratory signal, has become an adjunct treatment for a large range of psychologic and medical conditions. However, the underlying mechanisms explaining the effectiveness of HRV biofeedback still need to be uncovered. This study aimed to disentangle the specific effects of HRV biofeedback from the effects of SPB realized alone. In total, 112 participants took part in the study. The parameters assessed were emotional (valence, arousal, and control) and perceived stress intensity as self‐report variables and the root mean square of the successive differences (RMSSD) as a physiologic variable. A main effect of condition was found for emotional valence only, valence being more positive overall in the SPB‐HRVB condition. A main effect of time was observed for all dependent variables. However, no main effects for the condition or time x condition interaction effects were observed. Results showed that for PRE and POST comparisons (referring, respectively, to before and after SPB), both SPB‐HRVB and SPB‐NoHRVB conditions resulted in a more negative emotional valence, lower emotional arousal, higher emotional control, and higher RMSSD. Future research might investigate psychophysiological differences between SPB‐HRVB and SPB‐NoHRVB across different time periods (e.g., long‐term interventions), and in response to diverse psychophysiological stressors. Abstract : Slow‐paced breathing (SPB) is usually realized using a biofeedback device. Our findings show for the first time that a short SPB session (5 min) realized without any biofeedback device have mostly similar psychophysiological effects compared with SPB realized with biofeedback (i.e., displaying the heart rate signal), with the exception of a more positive emotional valence in the biofeedback condition.